Different Levels of DNA Methylation Detected in Human Sperms after Morphological Selection Using High Magnification Microscopy. (11th April 2016) - Cassuto, Nino Guy; Montjean, Debbie; Siffroi, Jean-Pierre; Bouret, Dominique; Marzouk, Flora; Copin, Henri; Benkhalifa, Moncef
Abstract : Objective . To analyze DNA methylation levels between two groups of spermatozoa taken from the same sample, following morphological selection by high magnification (HM) at 6100x microscopy. A prospective study was conducted and studied 876 spermatozoa from 10 randomly selected men. Sperm morphology was characterized at HM according to criteria previously established. High-scoring Score 6 and low-scoring Score 0 sperm were selected. Sperm DNA methylation level was assessed using an immunoassay method targeting 5-methylcytosine residues by fluorescence microscopy with imaging analysis system to detect DNA methylation in single spermatozoon. Results . In total, 448 S6 spermatozoa and 428 S0 spermatozoa were analyzed. A strong relationship was found between sperm DNA methylation levels and sperm morphology observed at HM. Sperm DNA methylation level in the S6 group was significantly lower compared with that in the S0 group (p < 10 - 6 ), OR = 2.4; and p < 0.001, as determined using the Wilcoxon test. Conclusion . Differences in DNA methylation levels are associated with sperm morphology variations as observed at HM, which allows spermatozoa with abnormal levels to be discarded and ultimately decrease birth defects, malformations, and epigenetic diseases that may be transmitted from sperm to offspring in ICSI.